Uso de sombreamento sobre índices térmicos, respostas fisiológicas e desempenho de bezerras cruzadas ½ Holandês x ½ Jersey a pasto - Barbosa, Luana Souza (2012)
Extensive bovine production in hot climate regions can be improved with the use of artificial shades in order to mitigate heat related stress. The objective of this work was to evaluate the influence of artificial shading on thermal comfort indexes, physiological variables and performance of dairy heifers raised in pastures. The experiment took place at the Kiwi Agropecuária in Silvânia-GO. Sixteen ½ Holstein x ½ Jersey dairy heifers with an average live weight of 93, 2 ±2,0 kg were used. Data were collected over a period of 115 days, during the months of June through September, 2011. It was used the randomized design, with two treatments and eight repetitions per treatment, where one was the Control Pasture – absence of shading, and the other was the Artificial Shading Pasture – artificial shading with polipropilene mesh providing 80% of shade/protection from direct sun light. Physiological variables measured included respiratory frequency, surface skin temperature and rectal temperature (at 09:00h and at 14:00h), and transpiration rate (at 14:00h). Animals were weighted every 14 days for performance evaluation. The environmental conditions were monitored by recording the air temperature, relative humidity, wind velocity and black globe temperature, exposed to direct sun light and in the shade. Values were recorded every two hours from 08:00h to 18:00h. The calculation of the temperature and humidity index (THI), the globe temperature and humidity index (GTHI), and the radiant termal charge (RTC). It were observed statiscal diferences for the physiological variables (P<0,01). The higher values of rectal temperature (34 x 39°C), respiratory frequency (70 x 77 mov.min.) and skin surface temperature (34,1 x 39,7°C) were observed in the animals in pastures with absence of shading (Control Pasture) and exposed to direct sun light when compared to the animals with access to artificial shading (Artificial Shading Pasture). No differences (P>0,01) were observed for average transpiration rate values. Weight gain was not different, with values of 0,705 kg/LW (Artificial Shading Pasture),and of 0,658 kg/LW (Control Pasture). Treatments were statiscaly different as far as dry bulb temperature, black globe temperature, THI, GTHI and RTC (P<0,01), with the lower values being observed in the shading environment. It can be concluded that the use of artificial shading in pastures promoted an improvement in comfort indexes and favored thermal regulation physiology without affecting the heifers´ performance.